Tingkat Kematangan Gonad Kepiting Bakau (scylla serrata) di Kawasan Hutan Mangrove Sicanang Kecamatan Medan Belawan Sumatera Utara (Gonad maturity level mud crabs(Scylla serrata) in the mangrove area Sicanang, Medan Belawan North Sumatera) - Alfredyanto Sianturi; Mohammad Basyuni; Zulham Apandy (AQUACOASTMARINE, 2016)
Mud crabs in the mangrove ecosystem play an important role and potentialcommodity, however the population has decreased. Knowledge level of maturity of gonadmud crab is very important to note because this level illustrating the ability of aquatic animalsto reproduce in order to remain sustainability.The aim of the research is to know the effect ofdifferent density on the gonad maturity and difference in carapace length with the maturitylevel of gonad in the mangrove area of Sicanang Medan Belawan, North Sumatera.Theresearch has been analyzed in July-September 2015 in Sicanang Medan Belawan, NorthSumatera. The research using purposivesampling method that consists of 3 stations. Mudcrabs (Scylla serrata)are captured using traps and observed level of maturity gonad. The totalwere amount 66 mud crab tails. Respectively gonad maturity level mud crabs in the period inJuly was I. 50 %, II. 36,36 %, III. 4,54 %, IV. 9,09 %. Gonad maturity level mud crabs in theperiod in August is I. 60,86 %, II. 30,43 %, III. 4,34 %, IV. 4,34 %. Gonad maturity levelmud crabs in the period in September was I. 57,14 %, II. 19,04 %, III.14,28 %, IV. 9,52%.The gonad maturity level V was not found in all stations. Between the carapace with thematurity indexs of gonads Correlation coefficientwas 0.907 . Carapace correlation with thelevel of maturity of gonad mudcrab is close.Keywords : Mud Crab, Gonads; Gonad maturity, Carapace